Pengaruh Kinerja Pegawai dan Mutu Pelayanan Publik terhadap Kepuasan Masyarakat pada Unit PATEN Kecamatan Campurdarat Kabupaten Tulungagung - Ike Sri Wahyu Nengseh (Universitas Islam Kadiri, 2023)
The purpose of the study : (1) analyze the effect of employee performance and public service quality on community satisfaction at the PATEN unit, Campurdarat District, Tulungagung Regency; (2) analyzing the effect of employee performance on community satisfaction in the PATEN unit, Campurdarat District, Tulungagung Regency; (3) analyzing the effect of public service quality on community satisfaction in the PATEN unit, Campurdarat District, Tulungagung Regency. This study uses a quantitative approach. The data collection instrument is in the form of a questionnaire. While the method of data analysis using descriptive statistical analysis and inferential statistical analysis with the help of the SPSS computer program. The results of the study: (1) the first hypothesis is accepted, that community satisfaction is influenced by employee performance and the quality of public services at the PATEN unit, Campurdarat District, Tulungagung Regency: (2) the second hypothesis is accepted, that community satisfaction is influenced by employee performance at the PATEN unit, Campurdarat District, Tulungagung Regency ; (3) the third hypothesis is accepted, that community satisfaction is influenced by the quality of public services at the PATEN unit, Campurdarat sub-district, Tulungagung Regency.